The diagnostics of colorectal cancer - Świderska, Magdalena; Choromańska, Barbara; Dąbrowska, Ewelina; Konarzewska-Duchnowska, Emilia; Choromańska, Katarzyna; Szczurko, Grzegorz; Myśliwiec, Piotr; Dadan, Jacek; Ładny, Jerzy Robert; Zwierz, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2014)
Colorectal cancer (CRC) is one of the most frequent human malignant neoplasms. CRC has an estimated incidence of more than 1,000,000 new cases annually worldwide. Approximately one out of three people who develop CRC dies from the disease. Furthermore, CRC often affects inhabitants of industrialized countries in comparison to less developed countries. Several markers of colon cancer, including CEA, CA-19-9, TPS, TAG-72 and lysosomal hydrolases, have been identified and are now being adopted in routine clinical practice. Increased values of these markers are often the first signal of recurrence or metastases, which is useful in prediction and prognosis of clinical outcome of patients with CRC. Determination of the activity of lysosomal exoglycosidases in body fluids may bring some hope of improving diagnosis of colorectal cancer. However, it has to be remembered that currently the most effective diagnostic method of CRC is endoscopy.